Pre-Travel Experiential Tourism Communication: A Study of Catalonia and Veneto - Nicolas-Alarcon, C (SAGE PUBLICATIONS LTD, 2025)
In response to the growing complexity of consumer choices, there has been a noticeable shift towards experiential marketing in travel destinations. This study focuses on Catalonia, Spain, and Veneto, Italy, examining how tourism institutions adapted communication to emphasise experiential appeals in the pre-travel phase. Using a content analysis of posts from Twitter-X, this study examines communication trends in aligning tourism products with the tourist experience, using pre- and post-COVID-19 pandemic periods as reference points. Although there have been attempts to diversify product categories, pre-pandemic categories remain dominant, limiting the comprehensive portrayal of tourism product offerings. This research proposes a framework for aiding pre-travel communication planning, advocating for the alignment of online branding of destinations with the projected destinations image based on experience dimensions and components.